Tangible consumption data landscapes of teenagers - Ağça, Ayşe Özge (Frontiers in Human Dynamics, 2025)
Teenagers are increasingly concerned about clean energy and play a crucial role in driving energy transition. In this study, I investigate how teenagers understand energy consumption, how tangible data mapping through anthropological theories may increase their awareness, and what ideas they may have about how to change habits. I present an approach for designing new data physicalizations, shaping how to facilitate data interaction sessions, and analyzing data physicalization and interactions based on Ingoldian concepts such as the Life of Lines and Imagining for Real. The empirical material includes 1-h sessions in two secondary education schools with 30 teenagers and video-recorded explanations about their consumption habits. The teenagers completed a questionnaire, drew a layout drawing of their home, and built a physical model of their home with products and rooms representing their energy consumption. The data landscapes encouraged participants to explore the perceptual integrity of energy-consuming habits and identify ways to change them. The self-expressive sessions demonstrate that the three data-mapping techniques enable teenagers to recount their daily consumption patterns. In particular, the tangible mapping of Consumption Data Landscapes can open avenues for engagement to increase their awareness of energy consumption and spawn responsibility for a change of habits.